Neoadjuvant vs. Adjuvant Chemotherapy in Muscle Invasive Bladder Cancer (MIBC): Analysis From the RISC Database - Del Bene, Gabriella; Calabrò, Fabio; Giannarelli, Diana; Plimack, Elizabeth R.; Harshman, Lauren C.; Yu, Evan Y.; Crabb, Simon J.; Pal, Sumanta Kumar; Alva, Ajjai S.; Powles, Thomas; De Giorgi, Ugo; Agarwal, Neeraj; et al. (Frontiers in Oncology, 2018)
Background: MIBC is an aggressive disease, with 5-year survival rates ranging from 36% to 48% for p T3/p T4/p N+tumors. Perioperative treatment can improve overall survival, with more robust evidence in favor of neoadjuvant chemotherapy. Few randomized studies have compared neoadjuvant and adjuvant therapy in bladder cancer. Consequently, it has been difficult to establish the benefit of adjuvant chemotherapy(AC) in MIBC. Methods:Data from patients with muscle invasive bladder cancer (>pT2) collected from 2005 to 2012 within the RISC data base (Retrospective International Study of Cancers of the Urothelial Tract) were evaluated. Overall survival(OS), cancer specific survival (CSS) and disease-free survival (DFS) between NC and AC generated using the Kaplan-Meier methodwere compared for MIBC by log-rank test. All patients in this analysis received either NC or AC. Results: A total of 656 patients with MIBC (325 treated with AC and 331 with NC) were analyzed. The median disease-free survival (DFS) was 37.6 months (95% CI:24.7-50.5) for NC vs 24.3 months (95% CI: 19.3- 29.3) with AC, with a reduction in the risk of disease progression of 21% in favor of NC (HR: 0.79, 95% CI: 0.63-0.99, p: 0.04). There were no significant differences in terms of CSS (HR: 1.21, IC 95%: 0.90-1.63, p: 0.21), and OS (HR: 1.22, 95% CI: 0.95-1.58, P=0.12). Conclusions: Within the limits of this retrospective study, this analysis suggests that NC is the best treatment for MIBC in terms of DFS. Nonetheless, CSS and OS were similar with both NC and AC strategies.